An Analysis of Loss Cost due to Road Clock on the Road Construction (Rigid Pavement) Reviewed by the Use of Oil Fuel - Nh, Ah. Syarifuddin; Lubis, Zulkifli (THE SPIRIT OF SOCIETY JOURNAL : International Journal of Society Development and Engagement, 2023)
This research was conducted against the background of road improvements on the road section in Ambeng-Ambeng Watangrejo village, Duduksampeyan, Gresik Regency along ± 1.5 km which caused traffic jams due to narrowing of road capacity. Vehicle travel time is very influential on the level of fuel consumption, because the longer the travel time experienced by a vehicle, the more fuel consumption will be. The length of congestion will affect the temperature of the vehicle engine which will get hotter which will eventually affect fuel consumption which will be more wasteful and this will result in a considerable material loss value. This study used quantitative research methods and direct surveys. The primary data used in this study included vehicle travel time and vehicle volume. The types of vehicles analyzed are several types of cars fueled by pertalite. Then the data is processed using references from the Indonesian Road Capacity Guidelines (PKJI 2014) and LAPI-ITB. The results showed that the loss of private cars (KR) fueled by the pertalite type was quite large, namely on Monday, the total loss during the 6 hours of research amounted to Rp.13.575.702 with an average hourly loss of Rp.2.262.617. As for Tuesday, the total loss during the 6 hours of research amounted to Rp.15.942.725 with an average hourly loss of Rp.2.657.121. And for Wednesday, the total loss during the 6 hours of research amounted to Rp.12.182.256 with an average hourly loss of Rp.2.030.376